Penerapan IoT pada Sistem Deteksi Kadar Air dan Level Tangki Stasiun SPBU - Hidayat, Andi Ircham; Agunawan, Agunawan; Mahendra, Yusri; Cahyani, Wanda (Universitas Negeri Gorontalo, 2023)
The development of the gas station business is currently very tempting for entrepreneurs, it can be witnessed that lately many gas station constructions have begun in the city to remote villages though. One of the most important things that is sometimes overlooked by gas station entrepreneurs is the quality of the fuel they sell and in general, monitoring the contents of the tank at gas stations is done manually. The purpose of the study was to design a Prototype of the Water Content Detection System and tank level, which aims to help gas station managers measure water content and monitor fuel content in gas station tanks automatically and realtime so that fuel quality is maintained, information can be monitored through web-based systems and mobile applications with Internet of Things technology. The IoT system design consists of an Arduino Uno R4 microcontroller, HC-SR04 ultrasonic sensor, conductivity sensor, and selenoid valve. The accuracy test results of the ultrasonic sensor used are good enough to measure the contents of the tank with an average error of 1.3%, while the conductivity sensor measurement has an average error of 0.292% with a validation process using the centrifuge method, The selenoid valve works well which is activated through a web-based monitoring application and a mobile application.